2023
DOI: 10.1002/msc.1798
|View full text |Cite
|
Sign up to set email alerts
|

Access to first contact physiotherapy appointments in primary care: A scoping review

Abstract: BackgroundFirst Contact Physiotherapy (FCP) is part of the drive to increase General Practice (GP) capacity by providing access to expert musculoskeletal (MSK) Physiotherapists in GP surgeries. For the FCP model to provide effective MSK care at the start of the patient's journey, it is essential that patients are directed to FCP appointments in a timely manner. It is therefore important to know how patients are accessing FCP appointments.ObjectiveTo provide an overview of the literature regarding patient acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It provides new evidence about patient reported facilitators and barriers to access, as well as confirming key access routes, and the challenges of low awareness of the FCPP role. A previous study found that there are a variety of access routes into FCPP appointments, with the most common way being booking via Reception (Lamb et al, 2023a); another study noted that many patients have seen or spoken to a GP about their MSK condition before receiving an FCPP appointment (Lamb et al, 2023b). In this current study, five of the 13 participants had only seen the FCPP after first having a GP appointment, and one of the patients' surgeries required a GP appointment prior to FCPP input.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It provides new evidence about patient reported facilitators and barriers to access, as well as confirming key access routes, and the challenges of low awareness of the FCPP role. A previous study found that there are a variety of access routes into FCPP appointments, with the most common way being booking via Reception (Lamb et al, 2023a); another study noted that many patients have seen or spoken to a GP about their MSK condition before receiving an FCPP appointment (Lamb et al, 2023b). In this current study, five of the 13 participants had only seen the FCPP after first having a GP appointment, and one of the patients' surgeries required a GP appointment prior to FCPP input.…”
Section: Discussionmentioning
confidence: 57%
“…The interview topic guide was informed by the aim of the research as well as by the results of the scoping review and survey of access methods previously performed by the authors (Lamb et al, 2023a(Lamb et al, , 2023b. It was developed by discussion among the authors, and there were no patients involved due to time constraints.…”
Section: Interview Topic Guide Developmentmentioning
confidence: 99%
“…The development of the survey questions was informed by a review of the research literature, which revealed a paucity of research on how patients access FCPP appointments, but which did provide some indication of potential access methods (Lamb et al, 2023). The questions were formulated to answer the primary and secondary research questions.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Different appointment booking processes such as 'triage at reception' and 'self-booking' were identified through a survey exploring FCPP provision across the UK (Halls et al, 2020), suggesting that there may be multiple and varied models in practice for accessing FCPP care; however, this was only one question in the survey and did not provide any further detail. A recent scoping review investigated the literature around how patients access FCPP appointments and found that there is little published evidence on this topic, and what evidence there is contains minimal description of the access routes and processes or their effectiveness (Lamb et al, 2023).…”
Section: Introductionmentioning
confidence: 99%